Relationship between obesity indices and cognitive function in Japanese men: A cross-sectional study - Satoshi Matsuno; Yuji Ozeki; Sayaka Kadowaki; Sayuki Torii; Keiko Kondo; Naoko Miyagawa; Azusa Shima; Mizuki Ohashi; Itsuko Miyazawa; Hiroyoshi Segawa; Takashi Hisamatsu; Aya Kadota; et al. (PLoS ONE, 2025)
We aimed to investigate the associations among various obesity indices, including visceral (VAT) and subcutaneous adipose tissue (SAT), and cognitive function in community-dwelling Japanese men. This population-based cross-sectional study used data of 853 men who participated in the follow-up examinations of the Shiga Epidemiological Study of Subclinical Atherosclerosis. Among them, we analyzed data of 776 men who completed the Cognitive Abilities Screening Instrument (CASI) and had abdominal VAT and SAT areas measured using computed tomography. The VAT-to-SAT ratio (VSR) was calculated; participants were categorized into VSR quartiles. Using analysis of covariance, we computed crude and adjusted means of the CASI total and domain scores across VSR quartiles, adjusting for potential confounders. No significant differences were observed in total CASI scores among body mass index, VAT, or SAT quartiles. However, in the multivariable-adjusted model, participants in the lowest VSR quartile (Q1) had significantly lower CASI total scores than those in the third quartile (Q3) (Q1: 89.5, Q3: 90.9). Low VSR was independently associated with lower cognitive function in a community-based sample of middle-aged and older Japanese men. In summary, VSR may be associated with cognitive function in Japanese men, highlighting the importance of fat distribution in cognitive health and highlighting VSR as a useful indicator.